Assessment of the Status of the Social Media Records: The Case of the Mpumalanga Government, South Africa. Issue 4 (2nd October 2019) - Netshakhuma, N. S.
Abstract: This paper assesses the status of social media records in the Mpumalanga Archives. The Mpumalanga Province (MP) faces challenges with regard to the management of social media records (SMR) due to the lack in the Mpumalanga Archives Act, No. 14 of 1998 of policy elements such as a preservation strategy, lack of capacity building, technological capabilities, collaboration, privacy, and the accessibility of social media. The International Records Management Trust-E-readiness Tool was used to assess the readiness of organizations to preserve SMR. The research findings show a lack of skills and knowledge in how to handle SMR and gaps in the act.